Analisis Pemanfaatan Media Penyiaran dalam Diseminasi Nilai-Nilai Keagamaan Islam: Studi Kasus Program Islam Itu Indah di TRANSTV - Rahman Hakim, Hari; Hidayah, Arina Rohmatul; Alisya, Mia; Khairunnisa, Khairunnisa; Bayu, Bayu (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This research examines the utilization of broadcast media in disseminating Islamic religious values through a case study of the program "Islam Itu Indah" on TRANSTV. The research method used is qualitative descriptive research with a case study approach. The main findings of this study include an analysis of the program's effectiveness in spreading religious values, public response and participation, and factors influencing the utilization of broadcast media in this context. The study aims to analyze the utilization of broadcast media in disseminating Islamic religious values through a case study of the program "Islam Itu Indah" on TRANSTV. The research method used is qualitative descriptive research with a case study approach. Data were collected through program content analysis, interviews with stakeholders such as producers, media observers, and program viewers, as well as observations of the public's response to the program. The results of the study indicate that the program "Islam Itu Indah" is effective in conveying religious values through broadcast media. The public's response to this program varies, with the majority expressing appreciation for the positive and inspirational portrayal of religious values. Factors such as high-quality program content, selection of credible speakers, and effective promotion strategies contribute to the success of this program in disseminating religious messages. However, there are also challenges faced, such as competition with similar programs, changing audience preferences, and criticism of religious representation in the media. Thus, this study not only provides an overview of the effectiveness of the "Islam Itu Indah" program in spreading religious values but also highlights the complexity and dynamics in utilizing broadcast media for religious purposes.The practical implications of this study include recommendations for developing more innovative and audience-relevant program content, more effective communication strategies to reach a wider audience, and efforts to enhance the production quality and promotion of religious programs in broadcast media. Therefore, this study makes a significant contribution to understanding the role of media in conveying religious messages and formulating more effective strategies for media utilization in a religious context.